International trade and investment dispute settlement : from rise to crisis and reform - Sacerdoti, Giorgio; Moran, Niall, 1988- (Routledge, 2025)
"This book provides a thorough comparative examination of the trade dispute settlement system of the WTO, Regional Trade Agreements, and of Investor-State Dispute Settlement (ISDS). Reviewing in parallel their origins, features, development, and current challenges, highlighting commonalities and differences, the book analyzes criticisms levelled against both regimes, explores current reform efforts at the WTO, ICSID and UNCITRAL (including the controversial proposal to replace ISDS with a Multilateral Investment Cour), and engages in the on-going debate by evaluating possible outcomes. As to trade, the book highlights the WTO system's successful operation for more than 20 years, and its hobbling functioning since the paralysis of the Appellate Body in 2019. As to ISDS, the book details the procedural protection granted to foreign investors under Bilateral Investment Treaties (BITs), other International Investment Agreements and investment chapters of trade agreements such as NAFTA, USMCA, CETA and the CPTPP, alongside the impact of case law on the regulatory space of states. This authoritative book will serve as a fundamental reference for students and researchers in international investment and trade law, as well as for international lawyers, adjudicators, and diplomats involved in dispute settlement"-- Provided by publisher.
Keywords: Dispute resolution (Law); Compromise (Law); Foreign trade regulation.; International commercial arbitration.; elektronické knihy; electronic books